Genetic Diversity of Osmophilic Yeasts Isolated from Indonesian Foods with High Concentration of Sugar - . RIDAWATI; BETTY SRI LAKSMI JENIE; ITA DJUWITA; WELLYZAR SJAMSURIDZAL (Indonesian Society for microbiology, 2010)
Isolation of osmophilic yeasts from a total of 70 samples consisting of jam, sweet condensed milk, honey, sweet soy sauce, and palm sugar was conducted. Sixty-eight osmophilic yeasts were isolated from strawberry jam, pineapple jam, and honey from South Sumatera. No yeast was obtained from condensed milk, honey from Sumbawa, sweet soy sauce, and palm sugar. Sequence analysis based on the ITS region showed that isolates were identified as five species belong to two genera, Candida and Sterigmatomyces. Those isolates were distributed in 5 species, C. metapsilosis, C. etchellsii, C. parapsilosis, C. orthopsilosis, and S. halophilus. C. etchellsii was the predominant species in South Sumatera honey, while C. parapsilosis group was predominant species in jams. Those species were reported as osmophilic yeasts. In both jams and honey we found C. parapsilosis and C. metapsilosis, whilst C. orthopsilosis was found only in pineapple jam. Phylogenetic analysis based on sequence of ITS region showed that most of the osmophilic yeasts (67 out of 68 isolates) were located in the phylum Ascomycota and only one isolate Sterigmatomyces halophilus NN38 from pineapple jam was located in the phylum Basidiomycota.